Broadchurch - Kelly, Erin, 1976-; Chibnall, Chris (Minotaur Books, 2014)
In the sleepy British seaside town of Broadchurch, Detective Ellie Miller has just returned from vacation, only to learn that she's been passed over for a promotion at work in favor of outsider Alec Hardy. He, escaping the spectacular failure of his last case, is having trouble finding his way into this tight-knit community wary of new faces. But professional rivalry aside, both detectives are about to receive some terrible news: 11-year-old Danny Latimer has been found murdered on the beach. For Ellie it's a personal blow; Danny was her older son's best friend. She can't believe anyone in Broadchurch would ever have harmed him. But Alec considers everyone, even Danny's parents, suspect in his death. It's a living nightmare for everyone involved...even before the press arrive and start stirring up the secrets every town member keeps hidden behind closed doors. An intimate portrait of a town and the ordinary grievances that have slowly simmered for years before boiling over in an unthinkable crime, this remarkable adaptation of the hit television show Broadchurch tells the story of a shattered family, a reeling town, and the two imperfect detectives trying to bring them answers"--